2022
DOI: 10.7759/cureus.21714
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Workup on Early-Onset Fibromyalgia: A Case Report

Abstract: This case report details a unique case of fibromyalgia manifested at a very early age, and the patient's suffering as a result of mis-and under-diagnosis of her condition for over a decade. For most of her life, the patient has had seemingly unrelated bouts of pain, neurological conditions, and psychiatric disturbances, and has seen numerous specialists for these conditions to no avail. The lengthy history discussion and physical examination findings, detailed in this report, revealed a progressive disease cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In particular, the patient had depression, anxiety, restless legs syndrome, elevated autoimmune titers, migraine, and possible Frontiers in Physiology frontiersin.org vulvodynia or vaginismus as comorbidities of FM (Treves and Qazi, 2022). Stehlik et al (Stehlik et al, 2009) found that 64% of a group of female patients diagnosed with FM also concurrently suffered from restless legs syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the patient had depression, anxiety, restless legs syndrome, elevated autoimmune titers, migraine, and possible Frontiers in Physiology frontiersin.org vulvodynia or vaginismus as comorbidities of FM (Treves and Qazi, 2022). Stehlik et al (Stehlik et al, 2009) found that 64% of a group of female patients diagnosed with FM also concurrently suffered from restless legs syndrome.…”
Section: Discussionmentioning
confidence: 99%